Communicating telecom fraud risk in anti-telefraud messages: The effects of metaphorical frames on attitudes - Liu, Mengna; Chen, Jinshi (Frontiers in Psychology, 2023)
With the frequent occurrences of telecom fraud crimes in China, it is very necessary and urgent to carry out effective anti-telefraud risk communication. In the present study, we investigated the role of metaphorical framing in shaping people’s attitudes towards telecom fraud in anti-telefraud messages through two experiments. Participants (N=547, Experiment 1; N=604, Experiment 2) were randomly assigned to war-framing, disease-framing, or issue-framing conditions. They were asked to read anti-telefraud messages where metaphorical frames were realized through multiple metaphorical expressions in Experiment 1 and relatively shorter messages where metaphorical frames were only instantiated through one metaphorical word in Experiment 2. The results showed that participants without prior experience with telecom fraud perceived severity as significantly higher in the war-framing condition than in the issue-framing condition. Besides, the framing effects were only detected in Experiment 2 where the short anti-telefraud message with limited metaphorical information was provided. The results of the study can shed light on public legal educators whose job is to use effective ways to communicate telecom fraud risk to citizens.